Respuesta :

Answer:

The last 2 statements are true

Step-by-step explanation:

given f(x) = x² + 6x and g(x) = 2x³

f(x) × g(x) = 2x³(x² + 6x) = 2[tex]x^{5}[/tex] + 12[tex]x^{4}[/tex]

not 2[tex]x^{5}[/tex] + 12x³

f(0) = 0 + 0 = 0 and g(2) = 2 × 2³ = 2 × 8 = 16

f(0 × g(0) = 0 × 16 = 0 ≠ 16

f(1) = 1 + 6 = 7 and g(1) = 2 × 1³ = 2

f(1) × g(1) = 7 × 2 = 14 ← True

g(x) × g(x) = 2x³ × 2x³ = 4[tex]x^{(3+3)}[/tex] = 4[tex]x^{6}[/tex] ← True

Answer: (C) f(1)·g(1) = 14      and       (D) g(x)·g(x) = 4x⁶

Step-by-step explanation:

f(x) = x² + 6x                 g(x) = 2x³

f(x) · g(x) = (x² + 6x)( 2x³)

              = 2x⁵ + 12x⁴           not equal to 2x⁵ + 12x³   (FALSE)

f(0) = 0² + 6(0)              g(2) = 2(2)³

     = 0 + 0                           = 2(8)

     = 0                                 = 16

            f(0) · g(2) = 0 · 16

                            = 0          not equal to 16 (FALSE)

f(1) = 1² + 6(1)                g(1) = 2(1)³

    = 1 + 6                            = 2(1)

    = 7                                 = 2

              f(1) · g(1) = 7 · 2

                           = 14         equal to 14 (TRUE)

g(x) · g(x) = (2x³)(2x³)

               = 4x⁶                 equal to 4x⁶ (TRUE)